Financial markets, developers and the geographies of housing in Brazil: A supply-side account. (May 2016) - Sanfelici, Daniel; Halbert, Ludovic
Financialisation and housing are predominantly associated to mortgages for homeownership and securitisation techniques. This paper looks at how financial markets influence the development industry, its business strategies, and the nature and location of its products. Adopting a supply-side account, the paper inquires into the rising role of financial markets as a source of funding for a consolidating development industry and its influence on the geography of housing in Brazilian cities. It develops the concept of resonance by combining two yet unrelated strands of literature on the study of financial markets (cultural economy and conventionalist economics). Narratives co-authored by the stock market community and development firms management over each individual firm, and the discursively linked strategic moves of developers, are shown to resonate, at the meso-level of the industry, into shared social representations (or conventions) on how to best assess and interpret the value of development firms. Analysing the wave of Initial Public Offerings occurring in the mid 2000s, the paper highlights that narratives of quick capital gains associated with the removal of the land banking bottleneck faced by developers supported a convention giving priority to the growth in total output, and contributed to the observed changes in the forms, scales and locations of housing projects in Brazilian cities. As discrepancies between the promises of returns for shareholders and actual financial results emerged, the growth convention unravelled, making way for other narratives and strategic moves to resonate anew and possibly change again the geographies of housing.